Entrepreneurship: Past Research and Future Challenges - Low, Murray B.; MacMillan, Ian C. (Journal of Management, 1988)
The contributions and shortcomings of past entrepreneurship research can be viewed within the context of six research design specifications: purpose, theoretical perspective, focus, level of analysis, time frame and methodology. The authors suggest a unifying definition of the field of entrepreneurship. The recent trend toward theory driven research that is contextual and process oriented is encouraging. It is time for entrepreneurship researchers to pursue causality more aggressively. Exploratory studies that are not theory driven should be discouraged unless the topic is highly original. Implications for practicing entrepreneurs are discussed.